“What can we do?”: A psychological perspective on (Mal)adaptive coping strategies and barriers to coping in an area of severe climate vulnerability in Bangladesh - Lilier, Kyra; Mikulewicz, Michael; Selim, Samiya A.; Raihan, Syed Tauheed; Islam, Rafia; Das, Jennifer; Danquah, Ina; Bärnighausen, Till; Sauerborn, Rainer; Bärnighausen, Kate (International journal of behavioral medicine, 2024)
As the mental well-being of billions of people is at risk due to the impacts of climate change, more research is required to better understand the psychological implications of climate vulnerability. This research aims to describe the coping strategies of a climate change affected population and the consequences of adaptation behavior.
Gesehen am 17.07.2025